2006
DOI: 10.1093/molbev/msj100
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure and Evolutionary History of a Diploid Hybrid Pine Pinus densata Inferred from the Nucleotide Variation at Seven Gene Loci

Abstract: Although homoploid hybridization is increasingly recognized as an important phenomenon in plant evolution, its evolutionary genetic mechanisms are poorly documented and understood. Pinus densata, a pine native to the Tibetan Plateau, represents a good example of a homoploid hybrid speciation facilitated by adaptation to extreme environment and ecological isolation from the parents. Its ecologically and reproductively stabilized nature offers excellent opportunity for studying genetic processes associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
66
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 63 publications
15
66
0
2
Order By: Relevance
“…However, the level of nucleotide diversity revealed in our study was in the same order or slightly higher than those reported for other conifers e.g., Cryptomeria japonica (π sil = 0.0039) over seven loci (Kado et al, 2003), Cathaya argyrophylla (π sil = 0.0024) (Wang and Song, 2006), Pinus tabuliformis, P. yunnanensis and P. densata (π sil = 0.0087 ~ 0.0128 over 7 loci, (Ma et al, 2006). It thus appears that contrary to previous suggestions Larix species have levels of nucleotide diversity comparable to other conifers.…”
Section: Discussionsupporting
confidence: 67%
“…However, the level of nucleotide diversity revealed in our study was in the same order or slightly higher than those reported for other conifers e.g., Cryptomeria japonica (π sil = 0.0039) over seven loci (Kado et al, 2003), Cathaya argyrophylla (π sil = 0.0024) (Wang and Song, 2006), Pinus tabuliformis, P. yunnanensis and P. densata (π sil = 0.0087 ~ 0.0128 over 7 loci, (Ma et al, 2006). It thus appears that contrary to previous suggestions Larix species have levels of nucleotide diversity comparable to other conifers.…”
Section: Discussionsupporting
confidence: 67%
“…This trend could be an indication that these populations were less severely affected by Pleistocene glaciations and the ensuing recolonization process than boreal species. Similarly, in Pinus species from the Tibetan plateau, the history of which has been less affected by glaciations, Tajima's D values tended to be positive (Ma et al, 2006). These different trends support the hypothesis that skews towards negative Tajima's D values in white spruce natural populations are likely resulting from demographic history, not from widespread hitchhiking effects.…”
Section: Ld and Selectionmentioning
confidence: 61%
“…The average π s values (0.00059 and 0.00003 in R. apiculata and R. mucronata, respectively) were one or two orders lower than those in other plant species (e.g., Cryptomeria japonica: π s = 0.0038 (Kado et al, 2003); A. thaliana: π s = 0.0083 (Schmid et al, 2005); Pinus tabuliformis, P. densata and P. yunnanensis: π s = 0.0087-0.0128 (Ma et al, 2006). Taking into account that five different nuclear loci totaling more than 5500 bp including more than 2900 bp of introns were investigated, the observed low levels of polymorphism appear to be a general feature of both R. apiculata and R. mucronata.…”
Section: Patterns Of Nucleotide Variationmentioning
confidence: 90%